Physical activity as a health factor modifying heart rate variability (HRV) - Nowosielska-Swadzba, Danuta; Zwolinska, Danuta; Jendrysek, Marek; Podstawski, Robert (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: The aim of the research was the evaluation of the selected HRV factors of the training volleyball players in two training periods and non-training people. Materials and methods : The study involved 8 leading volleyball players aged 20-23 and 13 non-training persons aged 19-26. The study of the training players was conducted twice: in the pre-competition and in the competition period. The study for the non-training persons was conducted once. The selected factors of the spectral analysis have been evaluated: TP [ms 2], share of LF and HF power [n.u], LF/HF indicator and time analysis factors: RR [ms], HR [1/min], RMSSD [ms]. Results : Statistically significant differences appeared only in the selected time analysis factors (RR, HR), between the group of the training and non-training persons. Other differences in the evaluated parameters were not statistically significant. Conclusions : Physical activity influences on the HRV growth. HRV measurement may serve for the control of the changes taking place in the AUN under the influence of the physical activity.